Abortion Law as Premeditated Murder: Assessing the Equality of Human and Fetal Rights to Life - Salsabila; M Razkiazka M H (PT. Pustaka Cendekia Publisher, 2025)
Abortion is a complex issue that involves legal, ethical, and religious debates regarding the right to life. This article argues that abortion should be treated as premeditated murder because it involves the deliberate termination of a human life. By examining the concept of the right to life as outlined in international law and bioethical perspectives, the article explores whether fetuses have the same rights to life as fully developed humans. It further delves into the implications of abortion as a violation of the right to life and the potential legal consequences of treating abortion as a premeditated crime. The article also reflects on how different countries’ abortion regulations align with or contrast the notion of protecting the fetus’s right to life.